USING MOVIE AS AUTHENTIC MATERIAL TO IMPROVE STUDENTS’ SPEAKING ABILITY - Aminah Ibrahim Abbad (Jurnal Bahasa Lingua Scientia, 2012)
English has four main skills that should be mastered by the students who learned it; they are listening, reading, speaking, and writing. This condition makes teacher try to find an appropriate teaching method for a better result in teaching English. Speaking is one of language skills that considered difficult to be learned by the eleventh grade students IPA 2 of GOC class MAN 2 Tulungagung. Sometimes teacher uses authentic material in the class to help the students in learning English and to bring a real condition in learning foreign language. In this study, the writer used movie as an example of authentic material. This study aimed to find out whether or not any significant effect of using movie in improving the students’ speaking ability. The research design of the study was experimental research with quantitative approach. The subject of this study was all of the eleventh grade students of IPA 2 GOC class MAN 2 Tulungagung. The instrument used to collect the data was test. In analyzing the data, the writer used simple quantitative measurement to find out the result.